RESISTANCE OF ESCHERICHIA COLI TO ANTIBIOTICS STEPTOMYCIN, KANAMYCIN, AND AMPICILLIN IN BROILER IN PENEBEL DISTRICT, TABANAN BALI - I Made Agus Wirawan; I Nengah Kerta Besung; Ketut Tono Pasek Gelgel (Buletin Veteriner Udayana, 2024)
Bacterial resistance has occurred in several antibiotics due to irrational use which makes treatment ineffective. This study aims to determine the resistance of Escherichia coli to the antibiotics streptomycin, kanamycin and ampicillin in broilers in Penebel District, Tabanan Regency of various ages. The research samples were isolated from broiler feces with a total of 20 samples of young broilers and 20 samples of adult broilers. This research used a randomized block design (RBD) by comparing the inhibition zones formed. The results of the sensitivity test using the Kirby-Bauer method of 40 E. coli isolates against streptomycin in young broilers were not resistant (0%), adult broilers were 30% resistant and 30% intermediate, to the antibiotic kanamycin there was no resistance (0%) in all age, and resistance to ampicillin has occurred in 10% of young broilers and 55% of intermediates, 65% of adult broilers and 10% of intermediates. There was a significant decrease in the zone of inhibition for the antibiotics streptomycin and ampicillin against E. coli between young broilers and adult broilers, whereas there was no significant decrease for kanamycin. Strict biosecurity and continuous sensitivity testing are needed so that disease prevention and treatment can be maximized.